Does Parental Bonding and Its Interaction with Child Temperament Influence Facial Affect Recognition in High-Risk Offspring for Developing Anxiety Disorders? - Ruci, Lorena (Université d'Ottawa / University of Ottawa, 2017)
Purpose: This thesis investigated whether perceived parental care and overprotection predicted accuracy of face emotion recognition in psychiatrically healthy youth. The study also examined whether child gender and having a parent with a history of anxiety moderated the relationship between parental bonding and facial emotion recognition, and whether behavioural inhibition mediated this relationship. Methods: The sample comprised 176 males and females aged 7-18 years. Participants completed the Parental Bonding Instrument, Childhood Self-Report of Inhibition, and the Ekman emotion recognition task. Results: Child gender and parental history of anxiety moderated the relationship between perceived parenting style and affect recognition. In boys, overprotection by father predicted deficits in recognizing fearful faces; in children with parental anxiety, low paternal care predicted deficits in recognizing angry faces; and in boys with parental anxiety, negative maternal bonding predicted deficits in recognizing expressions of surprise. Also, maternal overprotection predicted intensity of subjective anxiety while viewing expressions of surprise and happiness for all offspring, and behaviour inhibition mediated these relationships. Implications: The present study provides preliminary evidence that parental bonding interacts with risk group and gender in predicting accuracy of facial affect recognition in healthy youth. Further research is needed to confirm these findings and determine whether the interaction between gender, risk group and deficits in social cognition increase risk for developing pathological anxiety.
Keywords: Parental bonding; Facial affect recognition; Anxiety disorders; Anxiety disorders; High risk offspring; High risk offspring